2019
DOI: 10.24874/ijqr13.01-11
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Centers: What Are the Most Important Attributes in This Sector?

Abstract: Several studies have been conducted to identify the factors that most influence on service quality and customer satisfaction in the fitness industry. However, little attention has been dedicated to the identification of the most relevant attributes. This study aims to fulfill this gap and suggests that it is also necessary to identify the factors and the attributes which are most important concerning the perceptions of customers of fitness centers. Based on the scientific literature, a 23-item questionnaire wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…The interviews provided detailed data, accepting the cleanliness as the most influential tangible element. Considering previous research, the importance of clean environments, specifically in locker rooms, is evident [44,48,[64][65][66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interviews provided detailed data, accepting the cleanliness as the most influential tangible element. Considering previous research, the importance of clean environments, specifically in locker rooms, is evident [44,48,[64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…In the fitness market, there is no record of recent research on the best managerial practices. However, the study of fitness centers has allowed to know a number of key factors that lead to sustainable fitness centers [44]. Some research suggests that sports programs, personnel, and the physical environment are the most important attributes for fitness center management [23].…”
Section: Best Practices In Fitness Centersmentioning
confidence: 99%
“…Empirical evidence also introduces ambient conditions as a critical determinant of customer emotions in fitness centers (Freitas & Lacerda, 2019;Kim et al, 2016). In this extent, Naami and Hezarkhani (2018) showed that outstanding ambient conditions enhance the positive emotions of new customer, while reduce the negative ones.…”
Section: Theoretical Foundation and Hypothesis Developmentmentioning
confidence: 99%
“…The publications [17,18] are devoted to the topic of youth fitness. The publications [19][20][21] are devoted to the development of marketing strategies adopted for implementation at fitness clubs. The special role of fitness professionals' training is discussed in the works [22,23].…”
Section: A Analysis Of Publications That Addressed Aspects Of the Prmentioning
confidence: 99%